Tafsir Al-Qur’an dari dan untuk Orang Sunda: Ayat Suci Lenyepaneun Karya Moh. E. Hasim (1916-2009) - Jajang A Rohmana (Qur'an and Hadith Academic Society, 2020)
This article examines the peculiarities of one of Sundanese tafsirs or Qur’anic commentaries in West Java, Moh. E. Hasim’s Ayat Suci Lenyepaneun. Using discourse analysis approach, this study illustrates how the author arranges his interpretation in line with Sundanese culture and socio-religious background in modern Indonesia. There are some characteristics of Hasim’s Lenyepaneun: nuances of Sundanese literature and nature, Sundanese daily stories and his response to social-religious discourse. All these characteristics are significant in shaping the horizon of interpretation that feels more nyunda (Sundanese) as well as current response in his period. This study proves that the Sundanese tafsirs is not only related to deliver messages of God, but also associated with the functionalization of Sundanese as language of sense (rasa) to be more pervasive into hearts and minds. Lenyepaneun represents an effort of Sundanese domestication and bridging a gap between Arabic and Sundanese. This study also reinforces an illustration of how the text of Qur’anic commentary could serve as a social commentary. It could be one example of how local Qur’anic commentary in Indonesia could be a guardian of local Islam without leaving its relevance to the modernity.